A Simple and Effective Approach to Defatting Large Surface Area Full-thickness Skin Grafts - Cole V. Roblee, BS; Peter Mankowski, MD, MSc; Lauren Marquette, MD; Katherine M. Gast, MD, MS; William M. Kuzon, Jr, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Skin grafting is a fundamental tool in plastic surgery for the resurfacing of wounds resulting from burns, necrotizing infections, trauma, oncologic resections, donor site defects, and other causes. Compared with split-thickness skin grafts, full-thickness skin grafts (FTSGs) undergo less secondary contracture and often result in better aesthetic outcomes. To assure graft take, FTSGs require thorough defatting and adequate contact between the graft and the underlying wound bed. Conventionally, during the defatting process, FTSGs are stabilized on the surgeon’s fingers, whereas curved scissors are used to remove the subcutaneous tissue. This approach is effective for small grafts, but for large FTSGs, it is time-consuming and ergonomically challenging.